2003
DOI: 10.1111/j.1651-2227.2003.tb02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth characteristics and different dimensions of intellectual performance in young males: a nationwide population‐based study

Abstract: Aim: To study the effect of size at birth on different dimensions of intellectual capacity. Methods: The study comprised a population‐based cohort including all male single births without congenital malformations in Sweden from 1973 to 1976, and conscripted before 1994 (n= 168 068). Information from the Swedish Birth Register was individually linked to the Swedish Conscript Register. The test of intellectual performance included four different dimensions: logical, spatial, theoretical and verbal capacity. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…One speculative interpretation of the birthweight results was that birthweight could be an indicator of early development of the central nervous system, which in turn could be responsible for effect on work participation. We presented no data to support this, but the interpretation has some indirect support: there is a well-documented relation between birthweight and cognitive performance in adulthood (2)(3)(4)(5)(6)(7)(8) as well as in childhood (9)(10)(11)(12)(13)(14)(15)(16). The effect of birthweight is not limited to low or very low weights but extends well into the normal range (2-6,9-13).…”
Section: Introductionmentioning
confidence: 72%
“…One speculative interpretation of the birthweight results was that birthweight could be an indicator of early development of the central nervous system, which in turn could be responsible for effect on work participation. We presented no data to support this, but the interpretation has some indirect support: there is a well-documented relation between birthweight and cognitive performance in adulthood (2)(3)(4)(5)(6)(7)(8) as well as in childhood (9)(10)(11)(12)(13)(14)(15)(16). The effect of birthweight is not limited to low or very low weights but extends well into the normal range (2-6,9-13).…”
Section: Introductionmentioning
confidence: 72%
“…Not only brain 4,5 but also longitudinal catch-up growth 68,70 has been shown to be associated with a reduced risk of subnormal intellectual and psychological performance.…”
Section: Psychological and Psychosocial Manifestations Of Being Born Sgamentioning
confidence: 98%
“…[65][66][67] In a large Swedish survey, scores for intellectual and psychological performance of SGA male singletons tested at conscription were found to be lower compared to males born AGA; lower scores were found more frequently in males who did not show catch-up growth compared to those who experienced improved growth. 60,68 Long-term functional outcome of full-term infants born SGA has been addressed in a study of a British cohort of children born in 1970. Adults who were born SGA experienced significant differences in academic achievement and professional attainment compared with adults born AGA.…”
Section: Psychological and Psychosocial Manifestations Of Being Born Sgamentioning
confidence: 99%
“…[3][4][5][6][7] One recent report of critical periods found a strong association between postnatal head growth at 9 months and cognitive functioning at age 9 years, but no relation between head circumference in gestation or at birth with later neurodevelopmental outcomes at age 9 years. 8 Other studies have shown that small head circumference at birth can also predict poor intellectual performance in childhood and adulthood, 9,10 although this relationship appears to depend on the particular cognitive domain. 11 Head circumference is considered the most sensitive anthropometric measure of long-term malnutrition in infancy, 12,13 with caloric deprivation shown to be directly associated with suboptimal head growth.…”
Section: Introductionmentioning
confidence: 99%